ANALISIS PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORT TERHADAP KINERJA KEUANGAN (Studi Pada Seluruh Perusahaan Non Keuangan yang Terdaftar di BEI Periode 2014-2016) - Fadilla, Erika Putri (Aksara Public, 2018)
Population in this study refers to the all company except non financial companies that listed in Indonesia Stock Exchange Period 2014-2016. The technique used in this study is purposive sampling with 7 samples of the companies were selected which in the period of three years, so there were 21 samples data of companies listed in Indonesia Stock Exchange Period 2014-2016 are used.This study aims to examine the effect partially between Sustainability Report Disclosure to Return On Assets (ROA), Current Ratio (CR), Debt to Equity Ratio (DER) and Inventory Turnover (IT) on companies listed in BEI period 2014-2016. Methods of data analysis in this research is panel data regression analysis using Eviews 10.Based on the result of this research shows that partially Sustainability Report Disclosure have no effect on Return On Asset (ROA), Sustainability Report Disclosure have a positive and significant effect on Current Ratio (CR), Sustainability Report Disclosure have have no effect on Debt to Equity Ratio(DER), Sustainability Report Disclosure have have no effect on Inventory Turnover(IT.